Do students space their course study? Those who do earn higher grades. (February 2022) - Hartwig, Marissa K.; Malain, Eric D.
Abstract: We examined students' naturalistic decisions about spacing their study in an undergraduate course (N = 185) and whether self-selected spacing predicted course performance. Usage of two study tools – an online textbook and quiz tool – was recorded daily. We operationalized spacing as how often the tools were used and the timing of their use relative to exams. We found that students increased their study near deadlines and exams, used the textbook more often than the quiz tool, and used the tools infrequently when they were optional (vs. required). Importantly, spaced retrieval practice (via quiz tool) predicted course performance and GPA, whereas spaced reading (via textbook) was a weaker predictor. That is, when students opted for more frequent and early quizzing, they earned higher grades, even controlling for time spent quizzing. Thus, self-selected spaced study – especially spaced retrieval practice – supports student achievement. Highlights: We examined college students' decisions about spacing their study using behavioral trace data. We operationalized spacing as the frequency and timing of students' use of online study tools. Many students did not use the study tools when they were optional (vs. required). Greater spacing of study was associated with higher course performance and GPA. Spaced retrieval practice predicted grades more strongly than spaced reading did.